Structurally modified T-metal complexes and organic dyes as photosensitizers and earth-abundant T-metal catalysts for photo-driven hydrogen evolution in artificial photosynthetic systems. Issue 8 (25th March 2022) - Gupta, Rahat; Sahni, Priya; Sharma, Simran; Roy, Anindya; Pal, Amlan K.
Abstract : Production of green energy is important considering the depletion of fossil fuels and increase in greenhouse gases. Light harvesting T-metal complexes with earth abundant T-metal photocatalysts show promising ways of producing green energy. Abstract : The ever-persisting problem of energy crisis can be mitigated with renewable energy research leading to green energy sources, e.g., hydrogen. This work introduces explicitly photocatalytic hydrogen production employing 4d/5d-T-metal complexes and organic dyes as photosensitizers (PSs) and 3d-T-metal complexes (Co, Ni) with oxime, salen, porphyrin, and polypyridyl based ligands as catalysts. The review is focused on the judicious design of both PSs and catalysts to enhance the overall catalytic activity of artificial photosynthetic systems. Photoinduced electron transfer pathways involving the active sites of the catalysts have been made part of the discussion that elucidates how to design a robust and efficient photocatalytic hydrogen production system rationally. Reduction potentials of the catalysts and photosensitizers, change in the free energy values and DFT calculations have also been discussed to access the thermodynamic feasibility of the photo-induced electron transfer processes. Electrochemical studies, flash photolysis investigations, and various spectroscopic and microscopic techniques, e.g., photoluminescence, transient absorption, and emission, scanning/transmission electron microscopy studies, have been included in the discussion to validate the proposed catalytic mechanisms.